2018
DOI: 10.1017/cjn.2018.12
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Follow-Up Study in Patients with Guillain-Barré Syndrome

Abstract: Un an et trois ans après l'apparition des premiers symptômes du SGB, un nombre important de patients donnaient à voir des séquelles neurologiques, ce qui incluait une forme ou une autre d'incapacité fonctionnelle, des symptômes sensoriels, des douleurs et un état de fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
5
4
0
Order By: Relevance
“…Among all the patients included in our study, males were more affected. This was the same as in other studies, in which males accounted for over 50% of all the cases 5,22,23 . Our cases had a median age of 44 years, which was close to the average of some other studies, which ranged from 40 to 50 years 15,24 .…”
Section: Discussionsupporting
confidence: 90%
“…Among all the patients included in our study, males were more affected. This was the same as in other studies, in which males accounted for over 50% of all the cases 5,22,23 . Our cases had a median age of 44 years, which was close to the average of some other studies, which ranged from 40 to 50 years 15,24 .…”
Section: Discussionsupporting
confidence: 90%
“…The most common form in nerve conduction studies was AIDP, consistent with the literature (58% to 66.7%) 25 , 27 , 28 , 35 , 36 . The AMAN and AMSAN rates were 17% and 15%, respectively, consistent with a study in Chile that reported 26.7% axonal forms 27 .…”
Section: Discussionsupporting
confidence: 88%
“…Forty-nine percent of cases in the outcome evaluation had a degree of disability of 0 or 1, similar to the results of Thai and Canadian studies 28 , 35 . The last evaluations were performed via videoconference in some cases because of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In fact, there are many good population‐based studies available about disability 44 , 45 , 46 , 47 , 48 , 49 and quality of life 16 , 21 , 50 , 51 , 52 , 53 after GBS. The number of patients with poor functional outcomes differs between the studies 29 , 54 , 55 , 56 , 57 depending on the time interval after GBS, the definition of impaired function, symptoms analyzed, ICU treatment and necessity of mechanical ventilation, the studied population, and regional differences 44 as well.…”
Section: Discussionmentioning
confidence: 99%